PENGARUH PBL BERORIENTASI SOCIO-SCIENTIFIC ISSUE TERHADAP LITERASI SAINS DITINJAU DARI KEMAMPUAN AKADEMIK - Kurniawan, Muhammad; Palennari, Muhiddin; Jamaluddin, Asham Bin (Universitas Muhammadiyah Pontianak, 2024)
Science literacy is very important considering its role in the development of science and technological advancement. This means that during the learning process, students only memorise ideas and theories, but are unable to apply the ideas they have learned. Therefore, a learning model is needed that can encourage students to construct knowledge in their own heads and understand scientific phenomena that also involve the general public. The purpose of this study was to determine students‘ science literacy through the application of socio-scientific issue-oriented problem-based learning in terms of students’ academic ability in biology learning. As well as looking for the interaction effect of the application of socio-scientific issue-oriented problem-based learning with academic ability on science literacy in biology learning of grade X students. The research design used was Pretest-Posttest Non-Equivalent Control Group Design. The population of this study was Class X SMA Negeri 1 Wonomulyo consisting of five classes, samples used were Class X3 and X6. The results showed that (i) The average score of students taught with the Socio-Scientific Issue oriented Problem Based Learning model with a score of 70.29 (ii) The score criteria obtained from science literacy were in the High category. (iii) Science literacy of students taught with socio-scientific issue oriented Problem Based Learning learning model at high academic ability obtained an average score of 81.47 and students with low academic ability had an average score of 59.12. (There is no interaction effect between the model and academic ability on students' science literacy in biology learning.